2020
DOI: 10.5194/amt-13-6501-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of formaldehyde tropospheric columns in Australia and New Zealand using MAX-DOAS, FTIR and TROPOMI

Abstract: Abstract. South-eastern Australia has been identified by modelling studies as a hotspot of biogenic volatile organic compound (VOC) emissions; however, long-term observational VOC studies are lacking in this region. Here, 2.5 years of multi-axis differential optical absorption spectroscopy (MAX-DOAS) formaldehyde (HCHO) measurements in Australasia are presented, from Broadmeadows, in northern Melbourne, Australia, and from Lauder, a rural site in the South Island of New Zealand. Across the measurement period f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…Uncertainties in the dSCDs calculated by DOASIS are relatively small (<5%) for all three trace gases. This is as expected for urban MAX-DOAS NO 2 and O 4 Ortega et al, 2015), but lower than is typical for urban MAX-DOAS HCHO (Benavent et al, 2019;Heckel et al, 2005;Ryan et al, 2020b). This may be because HCHO dSCDs in Central London are three times larger than those over Melbourne, Australia in Ryan et al (2020b) and due to differences in HCHO wavelength ranges used by Heckel et al (2005) and Benavent et al (2019).…”
Section: Collocated Satellite and Surface Air Quality Observationssupporting
confidence: 66%
See 2 more Smart Citations
“…Uncertainties in the dSCDs calculated by DOASIS are relatively small (<5%) for all three trace gases. This is as expected for urban MAX-DOAS NO 2 and O 4 Ortega et al, 2015), but lower than is typical for urban MAX-DOAS HCHO (Benavent et al, 2019;Heckel et al, 2005;Ryan et al, 2020b). This may be because HCHO dSCDs in Central London are three times larger than those over Melbourne, Australia in Ryan et al (2020b) and due to differences in HCHO wavelength ranges used by Heckel et al (2005) and Benavent et al (2019).…”
Section: Collocated Satellite and Surface Air Quality Observationssupporting
confidence: 66%
“…The software corrects the raw spectra for dark current, electronic offset and stray light and convolves spectral cross sections of the analysed trace gases with the slit function of the instrument. Optimized wavelength ranges are 338-370 nm for NO2 and the O 2 -O 2 dimer (O 4 ), as recommended following a recent MAX-DOAS intercomparison campaign (Kreher et al, 2020), and 324.5-359 nm for HCHO, as this yields lower relative dSCD fit errors than the other commonly used fit range of 336-359 nm (Ryan et al, 2020b). O 4 is used to constrain aerosol impacts on the atmospheric light path.…”
Section: Vertical Profile Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…where N is the number of collocated pairs (days or months). We also derive correlation, slope and offset of the linear regression using the robust Theil-Sen estimator (Sen, 1968) as done in Vigouroux et al (2020).…”
Section: Data Use and Methodsmentioning
confidence: 99%
“…Daily satellite measurements have found that HCHO concentrations follow a spatial distribution similar to biogenic sources in the US, implying that biogenic emissions are a major source of HCHO. Biogenic sources emit isoprene that reacts in the atmosphere to form HCHO. More than 90% of the HCHO associated with biogenic sources forms through this secondary reaction pathway. ,, Identification of other HCHO sources using satellites is challenging. Most satellite studies average concentrations over weeks or months in order to remove the noise in the measurements.…”
Section: Introductionmentioning
confidence: 99%